Value addition in millets through agricultural processing techniques - Hemasankari, P; Rao, B Dayakar; Malathi, V M; Kiranmai, E; Rathnavathi, C V (Indian Farming, 2023)
Millets play a major role in eradicating the malnourishment and are poor man’s crop. Major millets include sorghum, bajra and ragi, and minor millets include proso, barnyard, little, foxtail and kodo millet. Value addition is defined as any activity that is done to improve the value of the product by both primary and secondary processing. Value addition in millets includes destoning, grading, cleaning and aspirating the dirt from the freshly harvested millets. Machines used in processing of millets generally reduce the drudgery of human effort and the time involved in processing. Dehulling is done for minor millets and polishing is done for major millets to make value added products. Puffed and flaked millets are produced to gain revenue for the underutilized marketable millets and to fetch most out of the millets.